A convenient synthesis and preparation of the derivatives of ethyl-6-(8-hydroxyquinolin-5-yl)-3-methylpyridazine-4-carboxylate as antimicrobial agents - Abdelmohsen, Shawkat Ahmed (European Journal of Chemistry, 2014)
Synthesis of ethyl 6-(8-hydroxyquinolin-5-yl)-3-methylpyridazin-4-carboxylate (4) via one-pot three component reaction of ethyl acetoacetate with (8-hydroxyquinolin-5-yl)(oxo) acetaldehyde (2) in the presence of hydrazine hydrate at room temperature in water was described. A new series of heterocyclic moieties such as oxadiazoles, triazoles, pyrazoles and Schiff bases were prepared and characterized. The structures of the newly synthesized compounds were established by elemental and spectral data. The antimicrobial activity of some of the synthesized compounds was examined against two Gram‐positive bacteria, two Gram‐negative bacteria and four fungi. The results showed that the tested compounds exhibited significant to moderate antimicrobial.